Numerical classification of some soils under rubber in Kerala - Rao D V K N; Jose A I (Journal of the Indian Society of Soil Science, 2002)
A test application was attempted with regards to numerical taxonomy in some rubber-growing soils of Kerala. The selection of the physiographic units was based in the resource map prepared by NBSS & LUP for Kerala. A total of eighteen soil profiles cut on top, middle and bottom reaches of slope in six prominant physiographic units under rubber were studied. Twenty-seven characteristics of soil profiles out of out of thirty-five as used by Arkley (1976) were taken for calculation of Euclidean distance. Using UPGMA (unpaired group method using arithmetic averages) a dendrogram was prepared. It could be seen that both soil taxonomy and numerical taxonomy could distinguish and group different soils. However, same taxon was grouped differently in numerical taxonomy. It was due to the quantitative differences in soil properties evaen in the same taxon, whereas in soil taxonomy certain fixed values of the atributes are used to classify the soils. Numerical taxonomy is a useful tool for classification of soils based on quantitative traits.
Keywords: Numerical classification; Rubber-growing soils; Soil taxonomy; Taxon